HYPOTHETICAL LEARNING TRAJECTORY FOR MULTIPLICATION USING RME AND ETHNOMATHEMATICS IN MBRU NIANG TRADITIONAL HOUSE CONTEXT - Tia Wulansari; Yandri Dami; Neni Mariana; Zaenal Abidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2026)
Researchers conducted a study on Hypothetical Learning Trajectory (HLT) of Multiplication Material Using the RME Approach Based on Ethno-mathematics with the Context of the Mbaru Niang Traditional House of Grade IV students of SDN Lidah Wetan II. This research was conducted in the 2023/2024 academic year at SDN Lidah Wetan II Jl. Raya Lidah Wetan No. 27, Lakarsantri District, Surabaya, East Java. This research aims to create more meaningful, interesting, and less boring mathematics learning for students. This research uses the Design and Research method. This research proves that using Hypothetical Learning Trajectory (HLT) can help understand students' learning trajectories in understanding multiplication material with media in the form of concrete objects, namely pictures of the Mbaru Niang traditional house, which can create more meaningful, interesting, and less boring mathematics learning. Data collection techniques used by researchers are documentation in the form of images and videos, LKPD work, and observation in the form of direct observation of students' conditions. Qualitative data collected by researchers are in the form of documentation results, LKPD work results, and observation results. This study employed a qualitative approach. The data analysis technique employed descriptive qualitative analysis. Based on this, it can be concluded that the Ethnomathematics-Based RME Approach using the Design and Research method can improve students' ability to understand multiplication.